Adobe Illustrator advanced - Uscilka, Deb; Safari eBooks ([Place of publication not identified] : [Intellezy], 2017)
"Adobe Illustrator is the premier drawing program used by artists and graphic designers to create vector images. In this advanced course, students will learn advanced type options including converting text to outlines, using type styles, working with area type options, threading type and wrapping text. Students will also learn to create swatch groups, recolor artwork, create and use blends, apply the gradient mesh and use Live Paint. In addition, students will transform shapes using various methods, work with the Symbol tools, import and trace images, create clipping masks and opacity masks. Finally, students will learn to create Actions to automate repetitive steps."--Resource description page.
Presenter, Deb Uscilka.
Title from title screen (viewed May 19, 2017).
Imprint from resource description page.
Keywords: Adobe Illustrator (Computer file); Computer graphics; Electronic books